2020
DOI: 10.18632/aging.103317
|View full text |Cite
|
Sign up to set email alerts
|

Highly expressed STAT1 contributes to the suppression of stemness properties in human paclitaxel-resistant ovarian cancer cells

Abstract: Signal transducer and activator of transcription-1 (STAT1) is an important factor in various cellular processes. The cancer stem cell (CSC) is considered as a tumor-initiating cell that drives the inner hierarchy in many cancers including epithelial ovarian cancer (EOC). Here, we explored for the first time the regulation of STAT1 on stemness properties in chemoresistant EOC cells. The paclitaxel (PTX)-resistant EOC cell line (OV3R-PTX) was derived from PTX-sensitive OVCAR-3 cells treated by the PTX regimen. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The human epithelial OC cell lines (OVCAR3, SKOV3, and A2780) and nontumorous human ovarian surface epithelial cells (HOSEpiC) were used as described previously (Zhang et al, 2017). The PTX‐resistant cells OV3R‐PTX and SK3R‐PTX were established in our laboratory (Wang et al, 2020). OVCAR3, A2780, and OV3R‐PTX cells were cultured in Roswell Park Memorial Institute‐1640 and SKOV3 and SK3R‐PTX cells were cultured in Dulbecco's modified Eagle medium (DMEM, 4.5 g/L glucose, Corning Inc.) with 10% fetal bovine serum (FBS, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human epithelial OC cell lines (OVCAR3, SKOV3, and A2780) and nontumorous human ovarian surface epithelial cells (HOSEpiC) were used as described previously (Zhang et al, 2017). The PTX‐resistant cells OV3R‐PTX and SK3R‐PTX were established in our laboratory (Wang et al, 2020). OVCAR3, A2780, and OV3R‐PTX cells were cultured in Roswell Park Memorial Institute‐1640 and SKOV3 and SK3R‐PTX cells were cultured in Dulbecco's modified Eagle medium (DMEM, 4.5 g/L glucose, Corning Inc.) with 10% fetal bovine serum (FBS, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…The PTX toxicity was detected using a CCK‐8 kit and cell resistance to PTX was measured by the half‐maximal inhibitory concentration (IC 50 ). Briefly, OV3R‐PTX cells were seeded in 96‐well plates at a density of 1 × 10 4 cells/well after COL5A1 knockdown for 24 h. The cells were then treated with different concentrations of PTX for 48 h. For the spheroid formation of cancer stem cells, the procedures were described previously (Wang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Our group is first to demonstrate the involvement of STAT1 in stemness and paclitaxel-resistance in OC cells ( Wang et al, 2020 ). We have found that a clone of paclitaxel-resistant cells shares the characteristics of CSCs and has stemness properties.…”
Section: Role Of Stat1 In Ovarian Cancermentioning
confidence: 99%
“…Signal transducer and activator of transcription 1 has been reported to enhance anti-tumor immune response and is considered to inhibit tumor growth ( Avalle et al, 2012 ). However, during tumorigenesis, malignant cells avoid the above impairment through downregulating STAT1 by the methylation of STAT1 in its promoter; the low expression level of STAT1 is observed in a chemoresistant cell line ( Wang et al, 2020 ). Thus, more attention should be paid to the effects of STAT1 on the significance of the TME, the integration of various signals, and the nature of tumor cells.…”
Section: Future Direction and Perspectivesmentioning
confidence: 99%
“…Human ovarian cancer cell line OVCAR-3 and human immortalized myelogenous leukemia cell line K562 were purchased from American Type Culture Collection (ATCC, Manassas, VA, USA). Human ovarian cancer PTX-resistant cell line OV3R-PTX referred to as DROV in the text was generated in this laboratory at Jinshan Hospital 32 and obtained a Chinese Invention Patent (# ZL201410708515.7). Human immortalized myelogenous leukemia doxorubicin (adriamycin, ADR)resistant cell line DRK562 was purchased from Keygen Biotech (Nanjing, China).…”
Section: Experimental Section Cell Lines and Cell Culturesmentioning
confidence: 99%